2016
DOI: 10.5644/ama2006-124.173
|View full text |Cite
|
Sign up to set email alerts
|

Accessory coracobrachialis muscle with two bellies and abnormal insertion - case report

Abstract: <p><strong>Objective</strong>. In the current study a brief review is presented of the coracobrachialis muscle’s morphological variability, action, embryological development and clinical significance. <strong>Case report</strong>. We report a case of a left-sided coracobrachialis muscle consisting of two bellies. The deep belly inserts into the usual site in the middle area of the anteromedial aspect of the left humerus, whereas the superficial belly inserts through a muscular sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Untreated snapping triceps syndrome can lead to severe fully‐symptomatic ulnar neuropathy (Jacobson et al, 2001; Paraskevas et al, 2016; Rioux‐Forker et al, 2018). In addition, a low‐lying insertion of the medial head of the triceps brachii and tendon insertion could predispose to UN entrapment, as noted by Beltran et al (2014).…”
Section: Elbowmentioning
confidence: 99%
See 1 more Smart Citation
“…Untreated snapping triceps syndrome can lead to severe fully‐symptomatic ulnar neuropathy (Jacobson et al, 2001; Paraskevas et al, 2016; Rioux‐Forker et al, 2018). In addition, a low‐lying insertion of the medial head of the triceps brachii and tendon insertion could predispose to UN entrapment, as noted by Beltran et al (2014).…”
Section: Elbowmentioning
confidence: 99%
“…Georgiev et al (2018) also report the presence of this aberrant muscle, but its origin was on the medial side of the body of the humerus, where it was fused with the distal part of the CBM. Paraskevas et al (2016) found a two‐bellied variant of the CBM; the deep head followed its usual course and terminated at the medial side of the body of humerus, but the superficial head ended at the MIMS and brachial fascia. The fibers of the CBM participated in creating a musculoaponeurotic tunnel containing the brachial vein and artery, the medial antebrachial cutaneous nerve, and both the median and ulnar nerves.…”
Section: Elbowmentioning
confidence: 99%